Characterization of the chloroplast genome of a rare species in China, Lilium martagon var. pilosiusculum - Yanping Zhou; Yu Bi; Qiheng Yan; Guixia Jia; Yunpeng Du (Mitochondrial DNA. Part B. Resources, 2018)
Lilium martagon var. pilosiusculum is an endangered species with high ornamental value in Xinjiang province (China). In this study, we reported a complete chloroplast genome of L. martagon var. pilosiusculum, which was de novo assembled using the next-generation sequencing data. The complete chloroplast genome is 152,816 in length, including a large single copy region of 82,265 bp and a small single copy region of 17,541 bp and two inverted repeat regions of 26,505 bp. A total of 110 functional genes were encoded, consisting of 76 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes. The overall AT content of the chloroplast genome is 63.00%. In addition, 68 SSRs and 31 large repeat sequences were found. In the maximum likelihood tree, a strong phylogenetic signal showed that L. martagon var. pilosiusculum is a species of lilium.